FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (PKB) DI UNIT PELAYANAN PENDAPATAN PROVINSI (UPPP) KABUPATEN SELUMA - Sari, R.A. Vivi Yulian; Susanti, Neri (JURNAL EKOMBIS REVIEW, 2014)
R.A. Vivi Yulian Sari, Neri Susanti; Factors That Influence Compliance With Taxpayers In Paying Tax On Motor Vehicles In The Province Revenue Service Unit Of Seluma Regency This study aimed to determine the factors that influence taxpayers compliance in paying motor vehicle tax (CLA ) in Unit Revenue Services of Province ( UPPP ) Seluma District. Type of this study is descriptive study. The population in this study is whousedtaxpayermotor vehicleisregisteredinthe Unit RevenueService of Province (UPPP) SelumaDistrict, witha sample of30taxpayer-wheeled motor vehicletwo (2) located atTaisMarket and registered inUnit RevenueService of Province of(UPPP) Seluma Districtin July2013.The data collected by usingquestionnaire. Data analyzed by using rating scale method. Taxpayer perceptions towards tax penalties showed a significant effect on tax compliance in carrying out its obligations to pay motor vehicle tax ( CLA ) , is seen from the position of the respondent's perception of the value of tax penalties perceptions of factors affecting tax compliance in paying taxes on motor vehicles in Unit Revenue Service of Province( UPPP ) Seluma District with the total score of 316 is in the interval 308-381 , agreed criteria.